2018
DOI: 10.1371/journal.pone.0202560
|View full text |Cite
|
Sign up to set email alerts
|

A voluntary conservation agreement reduces the risks of lethal collisions between ships and whales in the St. Lawrence Estuary (Québec, Canada): From co-construction to monitoring compliance and assessing effectiveness

Abstract: Lethal collisions with ships are limiting the recovery of several at-risk whale species worldwide. In the St. Lawrence Estuary (Quebec, Canada), the endangered blue whale and of special concern fin whale are among the migratory species subject to collisions with large ships. In 2011, a working group composed of representatives from the maritime industry, the government, non-governmental organizations, and academia was created to explore solutions to mitigate ship-whale collisions in the St. Lawrence Estuary. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In the face of uncertainty and in an effort to address impending environmental changes, adaptive management has been identified as the chief strategy to guide efficient decisionmaking (e.g., Margules and Pressey, 2000;Keith et al, 2011;Jones, 2016;Chion et al, 2018) and has already been discussed in the context of multi-drivers and cumulative impact assessments (Halpern et al, 2015b;Beauchesne et al, 2016;Côté et al, 2016;Schloss et al, 2017). Adaptive management can only be truly achieved through a commitment to adaptive monitoring and data reporting (Margules and Pressey, 2000;Halpern et al, 2012;Lubchenco and Grorud-Colvert, 2015).…”
Section: Adaptiveness Whymentioning
confidence: 99%
“…In the face of uncertainty and in an effort to address impending environmental changes, adaptive management has been identified as the chief strategy to guide efficient decisionmaking (e.g., Margules and Pressey, 2000;Keith et al, 2011;Jones, 2016;Chion et al, 2018) and has already been discussed in the context of multi-drivers and cumulative impact assessments (Halpern et al, 2015b;Beauchesne et al, 2016;Côté et al, 2016;Schloss et al, 2017). Adaptive management can only be truly achieved through a commitment to adaptive monitoring and data reporting (Margules and Pressey, 2000;Halpern et al, 2012;Lubchenco and Grorud-Colvert, 2015).…”
Section: Adaptiveness Whymentioning
confidence: 99%
“…Some studies have attempted to quantify the speed-risk relationship for specific whale species (Conn and Silber, 2013) or the hydrodynamic and impact forces in relation to speed (Silber et al, 2010). Others (e.g., Wiley et al, 2011;Chion et al, 2018) have evaluated the relative risk reduction that might be achieved by speed restrictions based on these speed-risk relationships. In addition to studies based on collisions, studies based on observations of whales close to vessels have inferred greater collision risks with increases in speed (Gende et al, 2011;Harris et al, 2012).…”
Section: Ship Strike Riskmentioning
confidence: 99%
“…Pilots in Southeast Alaska have found that, upon boarding the ship, communicating with the bridge team that whales may be encountered, emphasizing the importance of whale avoidance, and discussion of avoidance techniques has increased situational awareness of whales while in transit (similar to communicating local knowledge of navigational hazards) and, importantly, often reduced resistance to implementing proactive avoidance maneuvers or temporary reductions in ship speed. A recent study in the St. Lawrence Estuary demonstrated the value that marine pilots can have in implementing strike-risk reduction efforts, in part, through elevating its importance for the larger bridge team (Chion et al, 2018).…”
Section: Future Research and Trainingmentioning
confidence: 99%